Den kroppsliga differentieringens praktik: övervikt och nätdejting på intimitetens marknad (Sociologisk Forskning, 2010)
The practice of bodily differentiation: Overweight and internet dating on the market of intimacyWith the emergence of Internet dating, the procedure for choosing a partner has been radically changed. Given the initial invisibility of the body when Internet dating, one might presume that looks become less important when searching for partners online. Unfortunately, this is far from the truth. Based on twelve interviews with Internet daters of which six define themselves as overweight, the reproduction of bodily distinction in both mediated and direct communication is here being studied. A recurrent theme among the interviewees is the disappointment of the first date face to face. Ironically the importance of looks (or bodily capital) appears to be even more vital when dating on Internet than when building relationships “in real life”. Besides the disappointment of the first date in real life, the obese women in this study could also gather information of their value on the market of intimacy through being met by serious harassments and in exclusively being treated as sexual objects. Despite its strong association with the physical body, bodily capital can sometimes be difficult to distinguish from other forms of capital. From this point of view, the possibility of less repressive forms of intimacy is discussed.
Keywords: bodily capital; Internet dating; intimacy; choice of partner